Final years of the silver standard in Mexico: evidence of purchasing power parity with the United States - Bojanic, Antonio (História Econômica & História de Empresas, 2012)
This paper focuses on the use of silver as a monetary standard in Mexico during approximately the last three decades of the nineteenth century and the first decade of the twentieth century. During this period, several events occurred in the market for silver that affected those countries attached to this metal. These events caused some of these countries to abandon silver for good and adopt other types of monetary arrangements. Mexico and a few others chose to stay with it.The reasons behind this decision are analyzed. Additionally, evidence that supports the theory of purchasing power parity between Mexico and the United States is also presented and analyzed.